REPRESENTASI HIBRIDITAS GIRL POWER DALAM PENGEMBANGAN KARAKTER SRI ASIH - Salsabilla Nadhira, Alifya; Dwiningtyas Sulistyani, Hapsari; Bayu Widagdo, Muhammad (Interaksi Online, 2024)
This research is based on the idea that there has not yet been an Indonesian film featuring a female superhero main character with local cultural values. The film "Sri Asih," which premiered on the Disney+ Hotstar streaming platform, seeks to embody the hybridity of Girl Power through Indonesia's first superhero character, aiming to introduce a new alternative related to the identity of female superheroes and to serve as a form of resistance. However, there is a possibility that the strength displayed by the character Sri Asih may not fully resist but rather still reflects residues of dominant ideologies, given that the superhero film genre is highly profitable for the film industry. This study utilizes theories of girl power, cultural hybridity, and representation. The method employed is descriptive qualitative research with a critical paradigm and a critical discourse analysis approach following Sara Mills' framework. The research findings indicate that femininity and hybridity can be strengths and weaknesses in shaping the character of female superhero. Character analysis shows that the character embodies aspects of Girl Power by celebrating femininity, enjoying empowerment, being independent, and having agency to make choices. However, the character also demonstrates that anger and emotionality can be weaknesses attributed to women. The appearance (costume) of the superhero character demonstrates that cultural hybridity can present a new strength in forming the identity of female superheroes. However, the character's weapon is still influenced by cultural appropriation, where despite being part of Javanese culture, the function and logic of the scarf's power still resemble Western weapons.The fragmentation of the female body that emphasizes physical strength shows resistance against the stigma of the female body being considered passive, soft, and commodified, although it is not entirely free from the male gaze. Fragmentation of the face that emphasizes the pleasure of seeing Sri Asih's beauty illustrates a contradiction in portraying Indonesian superhero beauty with Western beauty standards. Focalization indicates that the character Sri Asih as a superhero has not yet fully become the subject of her desire to become a superhero, and her lineage remains crucial in bringing out female strength. Schemata analysis shows that although the character Sri Asih demonstrates femininity and hybridity as strengths through several aspects, the character still shows that women are "the other," and the cultural hybridity embodied through the identity of Sri Asih has not yet fully resisted the hegemony of dominant ideologies